ANALISIS KEMISKINAN DITINJAU DARI TEMPAT TINGGAL, PEKERJAAN, PENDAPATAN, DAN PENDIDIKAN DI SULAWESI SELATAN - Hasmin Hasmin (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
Poverty is a complex social problem, therefore handling must be complex. This paper aims to uncover the real conditions of the poor in South Sulawesi using resourch gounded. Research shows that poor people in South Sulawesi forced to live in slum housing or live in a cramped room, inadequate sanitation, and no proper health standards. They work in the informal sector as a handyman bentor, pedicab drivers, masons, fishermen, or agricultural laborers. This has resulted in their income is very low, the average median Rp5.218 per day per person or Rp36.526 per day per family, while the expenditure of the poor at Rp6.147 per day per person or at Rp43.031 per day per family. Low income causes a very low level of their education. The long -term problem if it is down to the next generation will be very dangerous for the survival of their families in particular and the next generation in general.